Ethnobotanical survey and therapeutic ranking of medicinal plants in Muzaffargarh, Pakistan: From traditional use to research priority - Khalid, Muhammad Usman; Sultan, Muhammad Tauseef; Okoduwa, Stanley Irobekhian Reuben (Ethnobotany Research and Applications, 2026)
Background: The use of medicinal plants in Muzaffargarh, Pakistan, remains poorly documented. This study systematically investigates and ranks the medicinal plants used by local communities, highlighting their therapeutic significance. Methods: A structured ethnobotanical survey was conducted with 79 informants across 40 communities, using semi-structured interviews and direct field observations. The Garrett ranking technique was applied to priorities medicinal plants by perceived efficacy. Ethnobotanical indices were used to assess the significance of plants. Results: Seventy-nine informants across Muzaffargarh District documented 75 medicinal plant species from 43 families. Quantitative ethnobotanical analysis using the Garrett-ranking technique identified Nigella sativa as the highest-ranked species, indicating strong community consensus for its use in metabolic and cardiovascular disorders. Zingiber officinale and Trigonella foenum-graecum were highly prioritized, reflecting their frequent use for digestive and metabolic health, while Moringa oleifera ranked among the top species for its perceived role in immune support and overall wellness. Decoction was the most commonly reported preparation method, followed by infusion, maceration, and powdered forms, with oral administration predominating. A statistically significant correlation (p < 0.05) was observed between the Relative Frequency of Citation and the Fidelity Level, indicating consistency between use frequency and perceived therapeutic specificity. Conclusions: The findings highlight the ethnopharmacological potential of these species, emphasizing the need for phytochemical validation and pharmacological studies. This study presents the first Garrett-ranked ethnobotanical assessment of medicinal plants in Muzaffargarh. These findings contribute to the preservation of traditional knowledge in Muzaffargarh District while emphasizing the need for careful validation of their efficacy and safety. Keywords: Ethnobotany, Ethnopharmacology, Medicinal plants, Muzaffargarh, Traditional knowledge.